2013
DOI: 10.1007/s00268-013-2047-0
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome and Quality of Life After Laparoscopic Treatment of Large Paraesophageal Hernia

Abstract: Long-term follow-up (up to 160 months) in our study showed that laparoscopic PEH repair is clinically efficacious but is associated with small anatomic recurrences in ≤50 % of patients. Further studies are needed to identify the anatomic, pathologic, and physiological factors that may impair outcome, allowing the procedure to be tailored to each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
2
22
2
9
Order By: Relevance
“…Respiratory symptoms, such as coughing and hoarseness, showed initial improvement, but at the long-term follow-up, this improvement was no longer statistically significant. This correlates with previous studies which suggest that the patient's respiratory symptoms are not as closely linked to the PEH as the gastrointestinal symptoms [19]. This was regardless of the radiologic status of the repair.…”
Section: Discussionsupporting
confidence: 78%
“…Respiratory symptoms, such as coughing and hoarseness, showed initial improvement, but at the long-term follow-up, this improvement was no longer statistically significant. This correlates with previous studies which suggest that the patient's respiratory symptoms are not as closely linked to the PEH as the gastrointestinal symptoms [19]. This was regardless of the radiologic status of the repair.…”
Section: Discussionsupporting
confidence: 78%
“…Dysphagia is a common side effect of the procedure, and an incidence of 13 % is reported in the literature [13]. This is in contrast with our findings in the quality of life questionnaires.…”
Section: Discussioncontrasting
confidence: 99%
“…In the elderly, the prevalence of GERD is nearly the same among the general population, but complicated GERD appears to be more common than in younger people ( Hazzard, 2001 ). Several authors have reported a higher incidence of esophagitis as well as Barrett esophagus in older patients ( Fass et al, 2000 ;Grant et al, 2013 ;Reynolds, 1996 ;Shaheen & Ransohoff, 2002 ;Targarona et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%